Peningkatan Perilaku Ibu dalam Pemenuhan Kebutuhan Gizi Baduta Berisiko Stunting melalui Pemberdayaan Kader - Demsa Simbolon; Meriwati Mahyuddin; Yenni Okfrianti; Ayu Pravita Sari (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Cadres are spearheading the success of monitoring the nutritional status of children under-two. Improving the knowledge, attitudes and actions of cadres through training, coaching and mentoring mothers in fulfilling the nutritional intake of under-two using the Nutrition Education Module has an impact on the success of the nutritional status monitoring function. Community service activities (PkM) are aimed at optimizing the role of cadres and families in fulfilling the New Normal Period undernutrition in Riak Siabun Village, Seluma Regency. The target audience is 10 posyandu and KPM cadres and 30 families with children aged 0-24 months. The activity is carried out with the stages of forming family companion cadres, training and coaching, as well as mentoring mothers of baduta. Evaluation of activities is carried out by measuring the knowledge, attitudes, and actions of cadres and mothers of baduta. The activity was carried out in January-November 2021. The data were analyzed by comparing the results of the pre-test and post-test. The results of community service activities showed that there was an increase in the score of knowledge, attitudes, cadres as well as the knowledge, attitudes, and actions of the mother under two for 3 months of mentoring. The results of the activity showed an increase in the average score of knowledge and attitudes before and after the training. The mentoring of 30 mothers of under-two showed an increase in the average score of mother's knowledge and attitudes about the fulfillment of nutrition for under-fives, mother's actions were still the focus of mentoring. Regulations in the form of policies and programs need to be improved to support cadre activities in assisting mothers of children under-two in the village.